Ionic Silicon Protects Oxidative Damage and Promotes Skeletal Muscle Cell Regeneration - Awad, Kamal (Int J Mol Sci, 2021)
Volumetric muscle loss injuries overwhelm the endogenous regenerative capacity of skeletal muscle, and the associated oxidative damage can delay regeneration and prolong recovery. This study aimed to investigate the effect of silicon-ions on C2C12 skeletal muscle cells under normal and excessive oxidative stress conditions to gain insights into its role on myogenesis during the early stages of muscle regeneration. In vitro studies indicated that 0.1 mM Si-ions into cell culture media significantly increased cell viability, proliferation, migration, and myotube formation compared to control. Additionally, MyoG, MyoD, Neurturin, and GABA expression were significantly increased with addition of 0.1, 0.5, and 1.0 mM of Si-ion for 1 and 5 days of C2C12 myoblast differentiation. Furthermore, 0.1–2.0 mM Si-ions attenuated the toxic effects of H(2)O(2) within 24 h resulting in increased cell viability and differentiation. Addition of 1.0 mM of Si-ions significantly aid cell recovery and protected from the toxic effect of 0.4 mM H(2)O(2) on cell migration. These results suggest that ionic silicon may have a potential effect in unfavorable situations where reactive oxygen species is predominant affecting cell viability, proliferation, migration, and differentiation. Furthermore, this study provides a guide for designing Si-containing biomaterials with desirable Si-ion release for skeletal muscle regeneration.